A Mechanism of methods used when working with documents and processing documents using artificial intelligence: Image recognition working mechanism (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
Automation of the processes of analysis, processing and transmission of information in thedevelopment of information systems reduces the complexity of implementation, time and material costs,frees up the resources of developers to solve more complex and creative tasks. The transition of documentmanagement now to electronic document management technologies not only dramatically accelerates thespeed of business processes of companies, but also provides cost savings when abandoning paper media, tominimize most operations when processing electronic documents, the use of artificial intelligencetechnologies is considered effective. In the article I will consider the possibilities of artificial intelligencetechnologies used in the process of enterprises, in converting documents into electronic and in the exchangeof electronic documents.Depending on the structure of the text, the review of the applied methods of artificial intelligence, neuralnetworks and the analysis of their work processes is carried out. Depending on the structure of the document,neural networks are used. Various recognition methods can be used for image recognition according to thecharacteristics of the recognized characters. The article describes the mechanism of image recognition, thedocument processing process, the operation of NLP algorithms. Processing documents of a professionalorganization with the help of artificial intelligence used in it improves the quality of the document flow ofthe enterprise, leads to time savings and cost reduction.
Keywords: Artificial intelligence, electronic document, neural network, recursive networks, NLP.